Influencia del tiempo y la granulometría en la recuperación de plomo mediante lixiviación por agitación usando ácido cítrico, en copelas usadas - Leyva Bazán, Gerges Dick (2017)
The present work titled "Influence of time and granulometry in the recovery of lead by leaching by agitation using citric acid in used cups" was carried out in the Laboratory of Mineral Processing of the Faculty of Engineering of the National University of Trujillo and had as purpose to show that the variables time and granulometry have a great influence in the recovery of lead, for that the bifactorial design was applied with 3 levels and 3 repetitions. The research work carried out has two variables: Time and Granulometry. The variable Time was studied at levels 30, 60, 90 minutes and the granulometry variable, with meshes of - # 50 # 70, - # 70 # 100 and - # 100 # 200. Each test was performed with 300 grams of sample, with solids percentage of 33.3%, agitation speed of 335 rpm and at ambient conditions. The study mineral was used test cups at the Laboratory of Mineral Processing of the Faculty of Engineering of the National University of Trujillo, after leaching according to the parameters mentioned above, the following result was obtained: according to the interaction for Recovery of Lead to different meshes worked, being the mesh - # 100 + # 200 which obtains a greater recovery of lead. In addition, with respect to the time to 90 minutes, a greater recovery of lead is obtained. After comparing the results obtained in the analysis of variance, with a confidence level of 95%, it is shown that the two variables of study influence significantly, and that their interactions also have significant difference on the recovery of lead